Fatigue and Cognitive Decline Associated With Depressive Symptoms Among Community-Dwelling Adults - Noura R. Almegbas PT, MSc; Gamar R. Almutairi PT, MSc; Rawan M. Alosaimi PT, MSc; Maha A. Alqahtani PT, MSc; Saleh G. Batook PT, MSc; Ibrahim A. Alfageh PT, MSc; Ahmed S. Alhowimel PT, PhD; Bader A. Alqahtani PT, PhD; Mohammed M. Alshehri PT, PhD; Aqeel M. Alenazi PT, PhD (SAGE Publishing, 2023)
To investigate the prevalence of depressive symptoms in community-dwelling Saudi adults aged ≥50 years and the associated risk factors. Patient Health Questionnaire 9 (PHQ-9) was dichotomized as depressive symptoms when the participants scored ≥10. Risk factors included age, sex, body mass index, education, employment, marital status, number of chronic diseases and medications, fatigue severity scale (FSS), and Montreal Cognitive Assessment (MoCA). Among the 206 participants, the prevalence of depressive symptoms was 17.48%. The number of chronic diseases, medications, and fatigue symptoms were significantly higher in those with depressive symptoms, whereas cognitive functions were significantly lower. Fatigue symptoms and cognitive functions were significantly associated with depressive symptoms. The cut-off scores for risk factors were ≥42 (FSS) and ≤23 (MoCA scale). Fatigue and cognitive impairments were the only risk factors that distinguished participants with and without depressive symptoms.